Catechin‐Rich Green Tea Extract and the Loss‐of‐TLR4 Signaling Differentially Alter the Hepatic Metabolome in Mice with Nonalcoholic Steatohepatitis. Issue 2 (10th December 2020) - Sasaki, Geoffrey Y.; Li, Jinhui; Cichon, Morgan J.; Kopec, Rachel E.; Bruno, Richard S.
Abstract : Scope: Catechin‐rich green tea extract (GTE) limits inflammation in nonalcoholic steatohepatitis (NASH) consistent with a Toll‐like receptor 4 (TLR4)‐dependent mechanism. It is hypothesized that GTE supplementation during NASH will shift the hepatic metabolome similar to that attributed to the loss‐of‐TLR4 signaling. Methods and results: Wild‐type (WT) and loss‐of‐function TLR4‐mutant (TLR4 mut ) mice are fed a high‐fat diet containing 0% or 2% GTE for 8 weeks prior to performing untargeted mass spectrometry‐based metabolomics on liver tissue. The loss‐of‐TLR4 signaling and GTE shift the hepatic metabolome away from that of WT mice. However, relatively few metabolites are altered by GTE in WT mice to the same extent as the loss‐of‐TLR4 signaling in TLR4 mut mice. GTE increases acetyl‐coenzyme A precursors and spermidine to a greater extent than the loss‐of‐TLR4 signaling. Select metabolites associated with thiol metabolism are similarly affected by GTE and the loss‐of‐TLR4 signaling. Glycerophospholipid catabolites are decreased by GTE, but are unaffected in TLR4 mut mice. Conversely, the loss‐of‐TLR4 signaling but not GTE increases several bile acid metabolites. Conclusion: GTE limitedly alters the hepatic metabolome consistent with a TLR4‐dependent mechanism. This suggests that the anti‐inflammatory activities of GTE and loss‐of‐TLR4 signaling that regulate hepatic metabolism to abrogate NASH are likely due to distinct mechanisms. Abstract : Wild‐type and Toll‐like receptor‐4 (TLR4) mutant mice are fed a high‐fat diet with green tea extract (GTE). Untargeted hepatic metabolomics reveal that GTE during nonalcoholic steatohepatitis (NASH) affects few metabolites consistent with a TLR4‐dependent mechanism. Whereas, GTE and the loss‐of‐TLR4 signaling independently affected a greater number of metabolites. Thus, GTE and the loss‐of‐TLR4 signaling distinctly affect the metabolome during NASH.